The last mermaid. Book 01 - Kim, Derek Kirk (Image Comics, Inc., 2024)
"A lone mermaid roams an endless wasteland on a quest beyond reason. To press ever onward, she must survive the interminable stretches between tiny pockets of water, roaming bands of cybernetic cannibals and fearsome mutant beasts. What propels her forward to take such a risk? And who is that cloaked figure watching her from afar...?"--